Legal effects in Spain of expropriations in Cuba. A fascinating journey through geopolitics and Private International Law - Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This paper deals with the issue of the international jursidiction of the Spanish courts to hear litigation for damages arising from expropriations and confiscations of property verified in other countries. The study analyzes the order rendered by the Provincial Court of the Balearic Islands (Spain) dated March 18, 2020 and focuses on the the need to adequately outline the State immunity exception, as well as the importance of correctly characterisation of the issue. Similarly, it is also shown that Spain lacks legal regulations such as the Helms-Burton Act in force in the United States of America.
Keywords: expropriations abroad; Helms-Burton Act; State immunity; damages; unjust enrich¬ment